2019
DOI: 10.3390/d11120231
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fixing and Phosphate Mineralizing Bacterial Communities in Sweet Potato Rhizosphere Show a Genotype-Dependent Distribution

Abstract: We hypothesize that sweet potato genotypes can influence the bacterial communities related to phosphate mineralization and nitrogen fixation in the rhizosphere. Tuberous roots of field-grown sweet potato from genotypes IPB-149, IPB-052, and IPB-137 were sampled three and six months after planting. The total community DNA was extracted from the rhizosphere and analyzed by Polymerase Chain Reaction-Denaturing Gradient Gel Electrophoresis (PCR-DGGE) and quantitative real-time PCR (qPCR), based on the alkaline pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…It is evident from this study that genotypes have a diminutive contribution towards shaping microbiome diversity [6]. On the contrary to that, previous studies reported a significant role of genotypes in selecting specific microbial groups in the rhizosphere [10,34,35]. Considering the functional profiling of a rhizosphere microbiome, our study has identified redundancy in the metabolic capacities of the bacterial communities with dominance of genes related to the metabolism and genetic processing categories.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…It is evident from this study that genotypes have a diminutive contribution towards shaping microbiome diversity [6]. On the contrary to that, previous studies reported a significant role of genotypes in selecting specific microbial groups in the rhizosphere [10,34,35]. Considering the functional profiling of a rhizosphere microbiome, our study has identified redundancy in the metabolic capacities of the bacterial communities with dominance of genes related to the metabolism and genetic processing categories.…”
Section: Discussioncontrasting
confidence: 51%
“…Several host–genotype-specific rhizospheric microbial community developments have been studied in many crops viz. peanut [ 6 ], soybean [ 11 ], sweet potato [ 35 ], tomato [ 44 ], rice [ 45 ], mulberry [ 46 ], and maize [ 47 ]. Most of the studies revealed that plant genotype plays a very small but significant role in shaping rhizospheric microbial association under diverse agroecological situations [ 48 , 49 ] in order to mitigate different stress conditions like phosphate starvation [ 50 ], nutrient mobilization [ 51 ], and plant growth promotion [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of bacteria has advantages in addition to promote plant growth, it is also able to protect plants from various plant disease infections. Several research results indicate that rhizobacteria are able to synthesize growth hormones, including IAA, gibberellin, and cytokinins [6], [7], [8], fix nitrogen [9], [10], [11] and dissolve phosphate [6], [12]. Meanwhile, as biological controllers for pathogens, rhizobacteria are able to produce compounds or metabolites such as antibiotics, HCN, siderophores, and secrete various hydrolytic enzymes that can degrade pathogenic cells [13], [14], [15].…”
Section: Introductionmentioning
confidence: 99%
“…A research paper by Marques and colleagues reports that sweet potato genotypes and their growth stage influence rhizosphere bacterial composition, in particular that of microbial groups involved in phosphate mineralization and nitrogen fixation, both playing a fundamental role in plant nutrition processes [8].…”
mentioning
confidence: 99%